Genetics and Functional Mechanisms of STAT3 Polymorphisms in Human Tuberculosis - Wang, Feifei; Huang, Guixian; Shen, Ling; Peng, Ying; Sha, Wei; Chen, Zheng W.; Shen, Hongbo (Frontiers in Cellular and Infection Microbiology, 2021)
Signal transducer and activator of transcription-3 (STAT3) plays an important role in biological balance. In-depth studies of single nucleotide polymorphisms (SNP) of STAT3 have not been done in human TB. Here, we investigated STAT3 SNPs using SNP scanTM technique in a case-control study of TB patients (n=470) and HC subjects (n=356), and then conducted functional studies of them using cellular models. We found that stat3 SNP rs1053004 TT and rs1053005 AA genotypes or T-A haplotype were associated with susceptibility to TB or TB severity. While the TT/AA genotype correlated with the low constitutive expression of stat3 and IL-17A in PBMC, the variant stat3 of rs1053004-rs1053005 T-A haplotype indeed reduced stat3 expression in reporter assays. Interestingly, host PBMC expressing the AA genotype and low constitutive stat3 exhibited the reduced ability to mount fast-acting innate immunity against mycobacterial infection in cellular models. Finally, mechanistic experiments showed that the STAT3 down-regulation broadly depressed STAT3 downstream anti-mycobacterial activities involving VDR-related CAMP pathways as well as IL-32, iNOS and autophagy mechanisms, leading to an enhanced mycobacterial infection. Together, our findings suggest that low constitutive stat3 derived from the TT/AA genotype/T-A haplotype acting to down-regulate STAT3, depresses downstream multiple anti-mycobacterial pathways/mechanisms, and then lead to an enhanced mycobacterial infection or TB in high-risk individuals.